PERAN PEMERINTAH DESA DALAM PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH DI DESA GABUGAN - Aris Tri Haryanto, Tutur Teguh Santoso, Liliek Winarni & (Transformasi, 2017)
The purpose of the research was to observe and analyze the role of Government inGabugan village of Empowering Micro small and medium in Gabugan. The researchmethod used is descriptive qualitative methods research informants. determinedby purposive technique. The results of research that the role of the Government of the village ofGabugan in the empowerment of small medium enterprises proved not optimal, because of lackof government programs that support small medium enterprises in the village of Gabugan toflourish. Her advice is pemeritah Gabugan village to empower small medium enterprisesexisting in the village of Gabugan with how to create training programs or other programs thatsupport small medium enterprises thrive.Keywords : small medium enterprises, village adminstration role